Tourism in Apuseni Mountains (Romania) - A technical proposal - Gheorghe Lucaciu; Marius Alin Marinău; Mirela Ștef; Dana Ioana Cristea; Dariusz Jacek Olszewski-Strzyżowski (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: The article presents the results of research on mountain tourism in the Apuseni Mountains in Romania, especially in the field of safety and health (physical condition) of participants of expeditions to the mountains and their knowledge about the risks that may be encountered in these destinations and the methods of informing about these threats (proposed markings and information about hazards in the mountains, and placed on hiking trails). Material and methods: 45 volunteer young people were involved in the research. The methods used were: 1) field testing method; we monitored the evolution of the heart rate and correlated it with the geographical area; 2) survey/questionnaire method; through a questionnaire, were subjectively identified the potentially hazardous areas and the reasons why they were considered as such; 3) direct observation method; we made a correlation between the subjective physiological response (accelerated breathing, suffocation, sweating) and the area in which they occurred. Results: Monitoring the evolution of the heart rate has allowed highlighting areas where prolonged physical exertion can generate a state of fatigue that can become acute, thus promoting decreased ability to pay attention and focus. The recommendation that accompanies the proposed tourist sign on several levels of intensity, induces the "obligation" of the recovery break, thus inducing the return of attention and the ability to concentrate. Other areas that may present a significant potential of risk or danger to tourists, by slipping or overloading muscles or areas with a complex geographical structure that require specific skills: balance, muscle strength, etc., have been identified using the questionnaire. Conclusions: Based on all the information collected, depending on the characteristics of the type of risk, we propose to complete the catalogue of tourist signs with more specific information. We assume that informative signs that we propose and the additional information they contain can contribute to the avoidance of some limit situations that would determine the occurrence of some incidents or accidents. The better educated and informed tourists are, the safer their way will be.